Optical manipulation of individual strongly absorbing platinum nanoparticles. Issue 46 (21st November 2017) - Samadi, Akbar; Bendix, Poul Martin; Oddershede, Lene B.
Abstract : Platinum nanoparticles have exceptional absorption in the near infrared (NIR) regime, thus leading to significant local heating. Nevertheless, they can be stably optically trapped in three dimensions by a tightly focused NIR laser beam. Abstract : Nanostructures with exceptional absorption in the near infrared (NIR) regime are receiving significant attention due to their ability to promote controlled local heating in biological material upon irradiation. Also, such nano-structures have numerous applications in nano-electronics and for bio-exploration. Therefore, significant effort is being put into controlling and understanding plasmonic nanostructures. However, essentially all focus has been on NIR resonant gold nanoparticles and remarkably little attention has been given to nanoparticles of other materials that may have superior properties. Here, we demonstrate optical control and manipulation of individual strongly absorbing platinum nanoparticles in three dimensions using a single focused continuous wave NIR laser beam. Also, we quantify how the platinum nanoparticles interact with light and compare to similarly sized absorbing gold nanoparticles, both massive gold and gold nanoshells. By finite element modeling, we find the scattering and absorption cross sections and the polarizability of all particles. The trapping experiments allow for direct measurements of the interaction between the nanoparticles and NIR light which compares well to the theoretical predictions. In the NIR, platinum nanoparticles are stronger absorbers than similarly sized massive gold nanoparticles and scatter similarly. Compared to NIR resonant gold nanoshells, platinum nanoparticles absorb less, however, they also scatter significantly less, thus leading to more stable optical trapping. These results pave the way for nano-manipulation and positioning of platinum nanoparticles and for using these for to enhance spectroscopic signals, for localized heating, and for manipulation of biological systems.